Age-stratified comparison of clinical outcomes between medical and surgical treatments in patients with unilateral primary aldosteronism - Ryo Nakamaru (Nature Portfolio, 2021)
Abstract Although adrenalectomy (ADX) is an established treatment for unilateral primary aldosteronism (uPA), the influence of age on the surgical outcomes is poorly understood. Therefore, we aimed to elucidate how age affects the clinical outcomes after treatments. We analyzed 153 older (≥ 65 years) and 702 younger patients (< 65 years) with uPA, treated either with ADX or mineralocorticoid receptor antagonist (MRA) in the Japan PA Study, and compared the estimated glomerular filtration rate (eGFR) or blood pressure over a 36-month period after treatments. ADX-treated patients showed severer biochemical indicators than MRA-treated patients. During 6 and 36 months, the eGFR decreased more prominently in older but not in younger patients with ADX than in those with MRA, which remained significant after adjustment with the inverse probability of treatment weighting (IPTW). There was a significant interaction between the age-groups and the treatment choices in the change of the eGFR with IPTW-adjusted analysis. The post-treatment dose of antihypertensive medication was lower in younger and higher in older patients with ADX than those with MRA. The clinical benefit of ADX differed between younger and older patients with uPA. These findings indicate the need for further validation on whether ADX can benefit older patients with uPA.